(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
This study examines the convergence and conflict between the General Agreement on Trade in Services (GATS) and the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) in the global trading system and their impact on market access and technology in developing countries. This study uses a normative legal research method with a qualitative, conceptual, and theoretical approach. Primary Legal Material refers to WTO provisions related to GATS and TRIPS, while secondary legal materials are in the form of journals, books, and related research. The analysis was conducted qualitatively using dependency theory and comparative advantage theory as analytical tools. The results of this study indicate that excessively strong protection of intellectual property rights can limit developing countries’ access to technology, knowledge transfer, and innovation. This condition increases the dominance of multinational companies and increases the dependence of developing countries on developed countries, especially in the digital technology, health, and education sectors. In addition, the relationship between GATS and TRIPS also has an impact on the digital sovereignty of developing countries because control of data, software, cloud computing, and artificial intelligence is still dominated by global companies from developed countries. Therefore, a more balanced international trade regulation is needed so that global trade liberalization does not only benefit developed countries, but is also able to encourage equal access to technology, national technological independence, and sustainable economic development for developing countries.